A C-Band Study of the Historical Supernovae in M83 with the Karl G. Jansky Very Large Array - Stockdale, Christopher; Long, Knox S.; Soria, Roberto; Cowan, John J.; Maddox, Larry A.; Winkler, P. Frank; Kunz, Kip D.; Blair, William P.; Miller-Jones, James (Proceedings of the Wisconsin Space Conference, 2012)
We present new low frequency observations of the grand design spiral galaxy, M83, using the C and L bands of the Karl G. Jansky Very Large Array (VLA). Utilizing the newly expanded bandwidth of the VLA, we are exploring the radio spectral properties of the more than 150 radio point sources in M83. We present the initial analyses, focusing on the radio evolution of the six historical supernovae discovered in the last century. With four epochs of VLA observations and optical and X-ray observations, we will probe the transition of supernovae into supernova remnants.Â 